Comparative Evaluation of the Corneal and Anterior Chamber Parameters Derived From Scheimpflug Imaging in Arab and South Asian Normal Eyes. Issue 11 (November 2015) - Prakash, Gaurav; Srivastava, Dhruv; Avadhani, Kavitha; Thirumalai, Sandeep M.; Choudhuri, Sounak
Abstract : Purpose: To evaluate the differences in the normal corneal and anterior segment Scheimpflug parameters in Arab and South Asian eyes. Methods: This hospital-based study was performed at a cornea and refractive surgery service in Abu Dhabi. A total of 600 consecutive normal candidates of South Asian (group 1, n = 300) and Arab (group 2, n = 300) origins underwent Scheimpflug imaging (Sirius; Costruzione Strumenti Oftalmici, Italy). One eye was randomly selected for evaluation. Results: The age and sex distributions in both groups were comparable. The pachymetric variables were statistically higher in group 2 (group 2 vs. group 1, 544.3 ± 32.2 μm vs. 535.1 ± 31.4 μm for central corneal thickness, 541.0 ± 32.6 μm vs. 531.9 ± 31.5 μm for minimum corneal thickness, 571.7 ± 43.2 μm vs. 558.1 ± 42.3 μm for apical thickness, and 58.1 ± 4.2 vs. 57.3 ± 4.3 mm 3 for the corneal volume; P < 0.05). The anterior chamber volume (group 2 vs. group 1: 166.4 ± 16.4 vs. 161.6 ± 20.5 mm 3 ) and angle (group 2 vs. group 1: 44.6 ± 6.2 vs. 43.5 ± 5.8 degrees) were also higher for group 2 ( P < 0.05). Central corneal curvature and apical corneal curvature (apex K) were higher in group 1 ( P < 0.05) with comparable astigmatism. The flat keratometry (K), steep K, and apex K were 43.6 ± 2.2 diopters (D), 44.9 ± 1.8 D, and 45.7 ± 1.8 D for group 1, and 43.1 ± 2.2 D, 44.5 ± 2 D, and 45.2 ± 1.9 D for group 2. The effect size (Cohen d) for significant parameters ranged from 0.2 to 0.3. Conclusions: Normal eyes of Arab ethnicity tend to have statistically thicker and flatter corneas and less-crowded anterior segments than those of the South Asian counterparts. These epidemiological differences have a mild to moderate biological effect size (Cohen d), but they should be considered when evaluating these eyes for anterior segment or corneal procedures.